Comparative Dendrochronological and 14C Dating of 15th Century Russian Icon. Issue 1 (2015) - Voronin, Konstantin; Dolgikh, Andrey; Matskovsky, Vladimir; Cherkinsky, Alexander; Skripkin, Vadim; Alexandrovskiy, Alexander
Abstract : A 15th century Russian icon from the Novgorod region was analyzed using both dendrochronological and radiocarbon methods [liquid scintillation counting (LSC) and accelerator mass spectrometry (AMS)]. This orthodox icon represents the Mother of God (Dexiokratusa). Fine art experts attribute the icon to between the late 14th to the early 15th centuries. The last complete tree ring was dated to AD 1409. There are indications that the trees were cut down during the summer of AD 1410. Taking into account the time for seasoning (about 8 months), the icon would have been painted in AD 1411. Wiggle-matching of the six AMS samples failed. Two of six AMS dates correspond to dendrochronological dates, while four of the six AMS dates showed differences with the dendrochronological dates by 5–39 yr. This discrepancy raises the issue of a possible regional offset from the calibration curve for the 13th century AD in NW Russia.